Methotrexate and risk of interstitial lung disease and respiratory failure in rheumatoid arthritis: a nationwide population-based study. (11th August 2020) - Ibfelt, Else Helene; Jacobsen, Rikke Kart; Kopp, Tine Iskov; Cordtz, René Lindholm; Jakobsen, Anna Svarre; Seersholm, Niels; Shaker, Saher Burhan; Dreyer, Lene
Abstract: Objectives: MTX is the most commonly recommended DMARD for first-line treatment of RA, however, it has been hypothesized to cause lung disease as an adverse effect. We investigated the risk of interstitial lung disease (ILD) and acute and chronic respiratory failure in persons with RA treated with MTX and other medications. Methods: From the Danish National Patient Register (NPR) and the DANBIO register for rheumatic diseases, we retrieved data on 30 512 persons with RA registered in 1997–2015. Information on ILD and respiratory failure was obtained from the NPR. Information on age and sex for all Danish citizens was obtained from the Danish Civil Registration System. MTX and other medication purchases were retrieved from the Danish Prescription Registry. Associations between MTX and lung disease outcomes were analysed in Cox regression models with adjustment for age, calendar time, sex and other medications. Standardized incidence ratios (SIRs) of lung disease were calculated to compare the RA population with the general population. Results: There was no increased risk of lung disease with MTX treatment [one or more purchases compared with no purchases; HR 1.00 (95% CI 0.78, 1.27) for ILD and 0.54 (95% CI 0.43, 0.67) for respiratory failure] at the 5 year follow-up. The SIR was three to four times higher for ILD in MTX-treated persons with RA, but similar to the whole RA population compared with the background population. Conclusion: Persons with RA had an increased risk of ILD compared with the general population, but there was no further increased risk associated with MTX treatment.